Evaluation of Hazelnut Husk as a Growing Medium in Primrose Cultivation - Damla Bender Özenç; Kökten Öz (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effects of hazelnut husk on growth, quality parameters, and nutrient content of primrose were evaluated. For this purpose, thirteen different growing media were prepared by mixing fresh hazelnut husk (FHH) and mature husk wastes (MHH) with peat at different rates. Some physical and chemical properties of the media and nutrient analyses were made for the nutritional status of the plants. The study was carried out in greenhouse conditions with four replications according to the randomized plot design. The aeration capacity and easily available content of the growing media is within the limit values, the medias with 50% FHH and MHH were prominent in terms of air-water balance. The effect of the medium on the aesthetic appearance, total shoot, leaf, and flower number of the primrose was not significant, but it was effective on flower weight, plant height, and root fresh-dry weight. In terms of plant root-shoot development, 30% FHH and 50% MHH were prominent. The media have caused significant differences in nutrient concentrations in primrose except for nitrogen, phosphorus, and copper. The leaf phosphorus concentration was high, nitrogen and potassium concentrations were within the limit value range, iron was sufficient, and manganese and copper were insufficient, while zinc was mostly lower than limit values. When all the data are evaluated, 50% ratios of hazelnut husks can be recommended in primrose cultivation and hazelnut husk can be evaluate in ornamental plant cultivation as a growing media.